P 17. Multichannel tDCS on the left DLPFC in healthy children and adolescents: A behavioral study. Issue 8 (August 2021) - Papadimitriou, K.; Splittgerber, M.; Borzikowsky, C.; Merschformann, C.; Salvador, R.; Brauer, H.; Breitling-Ziegler, C.; Prehn-Kristensen, A.; Krauel, K.; Nees, F.; Dempfle, A.; Siniatchkin, M.; et al.
Abstract : Introduction. Transcranial direct current stimulation (tDCS) is a non-invasive method of modulating brain activity. Previous studies with common tDCS montages have shown that there are positive effects on the left inferior dorsolateral prefrontal cortex (lDLPFC) for both healthy and clinical population like improvement of the working memory. Nevertheless, there is still lack of clear guidelines and safety instructions, probably due to not specific enough simulation montages, especially when focusing on pediatric population. This study aims to investigate behavioral outcome of multichannel tDCS over the lDLPFC in healthy children and adolescents. Therefore, tDCS was coupled with a memory task, especially focusing on accuracy and reaction time changes. Methods. The study was approved by the Ethic Committee of the Faculty of Medicine of Kiel University. The study was conducted in a double-blinded, randomized, sham-controlled design. 28 healthy children and adolescents (Age range: 10–17 years, mean age = 14, 18, SD = 2, 23) were included in the analysis. In four separate sessions, they received multichannel 2 mA anodal or sham tDCS for 20 minutes over the left DLPFC before or during working memory task (2 back task). At the behavioral level response time and accuracy for N-back task were evaluated. Additionally, safety and tolerability of multichannel tDCS has been investigated by written questionnaires. For multichannel 2 mA tDCS over DLPFC we used a 6-channel solution (3.14 cm 2 circular electrodes; AF3 (897 μΑ), AF7 (284 μΑ), F3 (819 μΑ), Fp2 (−1000 μΑ) und T7 (−1000 μΑ)). Before, during and after stimulation 32 channel EEG was recorded in order to demonstrate neurophysiological changes. All materials required for the stimulations and EEG recording were obtained from Neuroelectrics (Barcelona, Spain). Results. All participants tolerated the stimulation well. Our preliminary behavioral results showed that there were no significant effects on accuracy (ACC) or reaction time (RT) compared tDCS to sham stimulation. There were also no significant effects on ACC and RT between online or offline stimulation and no significant effects in the interaction of these variables ( p > 0.05). Conclusion. In summary, our study demonstrates that multichannel tDCS over DLPFC with 2 mA intensity over 20 min is well tolerated, and thus may be used as an experimental and treatment method in the pediatric population. Based on preliminary behavioral data, we could not show any stimulation effect. In accordance to literature though, stimulation often shows bigger effects on clinical population rather than healthy participants. Possible reasons for null findings could be ceiling effects (e.g. Suitability of the Paradigm depending on age). Furthermore, individual differences like baseline activity, may have had an impact on stimulation effectivity. Additional EEG analysis may provide more specific insights into developmental aspects of working memory processing on the neural level.